Ugotavljanje kakovosti prostorskih podatkov pri digitalizaciji prostorskega plana Republike Slovenije - Ivačič, Matjaž (Geodetski vestnik, 1997)
This paper describes a method for spatial data quality determination. Two institutions were involved in the project, the Office for Physical Planning and the Institute for Geodesy and Photogrammetry. The first phase of the project was the digitalization of spatial data needed in the process of physical planning. The second phase was the spatial data quality determination. The results show that spatial data quality determination must be part of all digitalization projects.
Keywords: geodezija; GIS; prostorski podatki; prostorsko planiranje; Slovenija